Synthesis and Electrochemical Performance of LiMnPO4 by Hydrothermal Method - Daichi Fujimoto; Yu Lei; Zheng-Hong Huang; Feiyu Kang; Junichi Kawamura (International Journal of Electrochemistry)
LiMnPO4 with olivinestructure which is the promising candidate for high voltage cathode material was synthesized by hydrothermal method. In order to synthesize high purity and well-defined LiMnPO4, several precursors for Li, Mn, and P sources and hydrothermal reaction parameters including temperature and [H2O]/[Mn] value are optimized. By analyzing the structure, Mn valence, morphology, and chemical ratio via XRD, XPS, Raman, SEM, and ICP LiMnPO4 synthesized from manganese acetate tetrahydrate have single phase of LiMnPO4 without impurity and showed charge and discharge reaction caused by Mn2+/Mn3+ redox. Specific capacity of synthesized LiMnPO4 grew up during cycling. Moreover, when hydrothermal temperature was set at 150°C and [H2O]/[Mn] value was set at 15, discharge capacity as high as 70 mAh/g was obtained at 1/20  C rate.